The U.D.C.A. on the Road to Environmental Sustainability in Its Infrastructure and Environment - Nieto, Maria Clara; Santiago, Henny Margoth; Beltran, Luis Eduardo (Journal of Sustainability Perspectives, 2024)
The Universidad de Ciencias Aplicadas y Ambientales U.D.C.A. has been walking a path from Sustainable Development to Environmental Sustainability, which is evidenced through initiatives in infrastructure and its environment, according to the Institutional Educational Project, which recognizes the Campus as a Living Classroom. In this opportunity, the process that is being advanced in terms of infrastructure and environmental management with three initiatives will be presented: 1. The U.D.C.A. environmental memory trail, an ecological trail under construction, which allowed articulating teaching, research, and social projection from a research seedbed of Environmental History, which collects environmental information related to biological, ecological and cultural aspects of the species of fauna and flora that are present on Campus. 2. The Tingua Refuge, an emblematic site of the UniversityUniversity recognized for its conservation of wild species such as Tinguas and ducks, where classroom projects are being developed with students of the Environmental Analysis Technology program to measure the quality of the water as a first step for its ecological restoration process, to turn it into a bio-indicator of environmental health for the UniversityUniversity. 3. The development of infrastructure as an axis of change toward the environmental sustainability of the University is part of the University's Infrastructure Master Plan, which defines the conditions under which the U.D.C.A. advances the necessary actions in environmental, urban, rural, and architectural aspects to adapt the academic spaces.